Juvenile hormone signaling in insect development and reproduction - Smýkal, Vlastimil (Jihočeská univerzita, 2014)
This thesis comprises three published papers and one manuscript, all focused on the role of juvenile hormone (JH), the JH receptor Methoprene-tolerant (Met) and its target gene Krüppel-homolog 1 (Kr-h1) in insect development and reproduction. The JH-Met-Kr-h1 pathway is critical for metamorphic transition in hemimetabolan Pyrrhocoris apterus (Hemiptera) and holometabolan Bombyx mori (Lepidoptera) but seems to be dispensable during early larval postembryonic development. The results also show that Met and its heterodimeric partner Taiman (Tai) but not Kr-h1 are critical for ovarian development and vitellogenesis in Pyrrhocoris females. In vitro, in vivo and cell-based techniques in Drosophila melanogaster have demonstrated that Met and its paralog Gce are a bona fide receptor for JH. Only Gce capable of binding JH rescued Drosophila deficient for Met and Gce proteins, and the capacity of Gce to bind JH was necessary for JH-dependent transcriptional activation by Gce and Tai.
Juvenile hormone signaling in insect development and reproduction
Keywords: bHLH-PAS; Insect development; Hormonal signaling; Insect metamorphosis; Juvenile hormone; Krüppel homolog 1; Methoprene-tolerant; Metamorphosis; Oogenesis; Vitellogenesis; bHLH-PAS; Insect development; Hormonal signaling; Insect metamorphosis; Juvenile hormone; Krüppel homolog 1; Methoprene-tolerant; Metamorphosis; Oogenesis; Vitellogenesis